Afterlives of Ancient Rock-cut Monuments in the Near East
1 online resource.
Keywords: This book concerns the ancient rock-cut monuments carved throughout the Near East, paying particular attention to the fate of these monuments in the centuries after their initial production. As parts of the landscapes in which they were carved, they acquired new meanings in the cultural memory of the people living around them. The volume joins numerous recent studies on the reception of historical texts and artefacts, exploring the peculiar affordances of these long-lasting and often salient monuments. The volume gathers articles by archeologists, art historians, and philologists, covering the entire Near East, from Iran to Lebanon and from Turkey to Egypt. It also analyzes long-lasting textual traditions that aim to explain the origins and meaning of rock-cut monuments and other related carvings.